Principles governing F1 hybridization in the genera Aeonium and Greenovia in La Gomera, Canary Islands - Arango, Octavio (Willdenowia, 2024)
A phytochorological and ecobiological study of the nine species, two subspecies and two varieties of the genera Aeonium and Greenovia in La Gomera is carried out, with special attention to F1 hybridization in nature. To the ten hybrids already described on the island, seven new hybrids were discovered, which are the subject of a separate publication. In all the known hybrids I determined whether the parents were sympatric or allopatric. The geographical coincidence of the parents was a sine qua non requirement for hybridization to occur in all the hybrids known so far, since pollen transfer by biotic and abiotic agents does not function between disjunct areas. The two prezygotic reproductive barriers that currently prevent interspecific hybridization in Aeonium or intergeneric hybridization between Aeonium and Greenovia are the geographic separation of populations and the different flowering times. The ability to survive and reproduce successfully of F1 hybrids in Aeonium and Greenovia is usually lower than that of the parent species and they generally disappear from the environment in the first filial generation without leaving offspring. The fundamental principles that govern F1 hybridization in La Gomera are extracted, and after verifying that they were also fulfilled in the other mountainous islands, they were synthesized in eight principles, which provide an updated vision of hybridization in the genus Aeonium. Citation: Arango O. 2024: Principles governing F1 hybridization in the genera Aeonium and Greenovia in La Gomera, Canary Islands. – Willdenowia 53: 257–268 Version of record first published online on 23 January 2024.